Pathogenesis of Prediabetes: Role of the Liver in Isolated Fasting Hyperglycemia and Combined Fasting and Postprandial Hyperglycemia - Basu, Rita (Endocrine Society, 2013)
CONTEXT: People with prediabetes are at high risk of developing diabetes. OBJECTIVE: The objective of this study was to determine the pathogenesis of fasting and postprandial hyperglycemia in prediabetes. DESIGN: Glucose production, gluconeogenesis, glycogenolysis, and glucose disappearance were measured before and during a hyperinsulinemic clamp using [6,6-(2)H(2)]glucose and the deuterated water method corrected for transaldolase exchange. SETTING: The study was conducted at the Mayo Clinic Clinical Research Unit. PARTICIPANTS: Subjects with impaired fasting glucose (IFG)/normal glucose tolerance (NGT) (n = 14), IFG/impaired glucose tolerance (IGT) (n = 18), and normal fasting glucose (NFG)/NGT (n = 16) were studied. INTERVENTION: A hyperinsulinemic clamp was used. OUTCOME MEASURES: Glucose production, glucose disappearance, gluconeogenesis, and glycogenolysis were measured. RESULTS: Fasting glucose production was higher (P < .0001) in subjects with IFG/NGT than in those with NFG/NGT because of increased rates of gluconeogenesis (P = .003). On the other hand, insulin-induced suppression of glucose production, gluconeogenesis, glycogenolysis, and stimulation of glucose disappearance all were normal. Although fasting glucose production also was increased (P = .0002) in subjects with IFG/IGT, insulin-induced suppression of glucose production, gluconeogenesis, and glycogenolysis and stimulation of glucose disappearance were impaired (P = .005). CONCLUSIONS: Fasting hyperglycemia is due to excessive glucose production in people with either IFG/NGT or IFG/IGT. Both insulin action and postprandial glucose concentrations are normal in IFG/NGT but abnormal in IFG/IGT. This finding suggests that hepatic and extrahepatic insulin resistance causes or exacerbates postprandial glucose intolerance in IFG/IGT. Elevated gluconeogenesis in the fasting state in IFG/NGT and impaired insulin-induced suppression of both gluconeogenesis and glycogenolysis in IFG/IGT suggest that alteration in the regulation of these pathways occurs early in the evolution of type 2 diabetes.